2022
DOI: 10.1186/s12887-022-03175-8
|View full text |Cite
|
Sign up to set email alerts
|

Child transmission of SARS-CoV-2: a systematic review and meta-analysis

Abstract: Background Understanding of the role of children in COVID-19 transmission has significant implications for school and childcare policies, as well as appropriate targeting of vaccine campaigns. The objective of this systematic review was to identify the role of children in SARS-CoV-2 transmission to other children and adults. Methods MEDLINE, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials, and Web of Science were electronically searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 80 publications
4
29
3
Order By: Relevance
“…Of the 59 households with confirmed cases, the child care case was the household index in 39 instances. This contrasts with studies that suggest no secondary transmission from school aged children (16) and reduced transmission from children to their households (17). Our findings of increased cases in children when a child is the index case is in contrast to another Silverberg et al finding (17) that children transmit to other children less readily, although another study suggested that children aged 0-3 were the most at risk for transmitting to their households (18).…”
Section: Discussioncontrasting
confidence: 99%
“…Of the 59 households with confirmed cases, the child care case was the household index in 39 instances. This contrasts with studies that suggest no secondary transmission from school aged children (16) and reduced transmission from children to their households (17). Our findings of increased cases in children when a child is the index case is in contrast to another Silverberg et al finding (17) that children transmit to other children less readily, although another study suggested that children aged 0-3 were the most at risk for transmitting to their households (18).…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the increased likelihood of asymptomatic presentation of children infected with SARS-CoV-2 does not account for the differences in infectiousness between adults and children. [29] The overall estimated household SAR of 13.0% is comparable with estimates from studies in China that also used a statistical transmission model with similar parameters (10.4% and 12.4% for incubation period of 5 days and a 13-day infectious period). [14,30] However, studies that used estimates from primarily binomial models before and after the emergence of the omicron variant estimated a higher household SAR across settings; [2,28,31] while many factors may explain this difference, the use of binomial models rather than statistical transmission models likely bias the estimated SAR upwards.…”
Section: Discussionsupporting
confidence: 67%
“…In the context of ongoing public health measures and vaccination programs, it is crucial to keep monitoring humoral immunity. Children have not been equally represented in immunosurveillance, while they do play a role in the transmission of SARS-CoV-2 (1). Surveillance of immunity in children is important to establish effective public health measures for this group.…”
Section: Introductionmentioning
confidence: 99%